Scaling K-indices without subjectivity - Rangarajan, G. K.; Murty, A. V. S. (My University, 1980)
A new approach to scaling the K-indices of magnetic activity through the Method of Natural Orthogonal Components (NOC) is outlined. This procedure, which completely eliminates subjectivity in determining the quiet day variation should prove useful in standardizing the K-scaling at all magnetic observatories. A Fortran IV computer programme is available on request from the authors.
Keywords: K-Indices; Natural orthogonal components; Magnetic observations; K-scaling; Magnetic activity